Una aproximación al derecho fundamental a la propiedad privada desde una perspectiva multinivel - Sarrión Esteve, Joaquín (Revista de Derecho Político, 2017)
Resumen: El derecho a la propiedad forma parte indiscutible de la historia y evolución del constitucionalismo, y encuentra su reconocimiento en el artículo 33 de la Constitución Española delimitado por su función social. Cuando se van a cumplir 40 años de nuestra Carta Magna es un buen momento para realizar una revisión de su configuración en nuestro sistema constitucional y, teniendo en cuenta la apertura de nuestro texto constitucional, aproximarnos al mismo desde una perspectiva multinivel, atendiendo por tanto a la importancia de su configuración en el nivel externo, en especial en el Convenio Europeo de Derechos Humanos y en el Derecho de la Unión Europea. Summary: 1. Motivation. 2. Private property at the internal level. Special atention to its configuration within the spanish constitution. 3. Private property at the external level. Special atention to its configuration within the echr and the eu law. 4. Concluding remarks. 5. Bibliographic references. Abstract: The right to property is an indisputable part of the Constitutionalism’s history and evolution. It is recognised in the artículo 33 of the Spanish Constitution where it is delimited by its social function. In a moment when we are going to celebrate our Constitution’s 40th anniversary, it is a good time to carry out a review of its configuration in our constitutional system. And taking into account the opening of our constitutional text, it is also important to approach to it from a multilevel perspective, i.e., taking into account the importance of its configuration at the external level, in particular the European Convention on Human Rights and the European Union law.